Niobium Pentoxide as an Acid Catalyst: An Overview - Ana Paula de Melo Guedes; Débora Luísa Rosendo Tomé De Miranda; Amanda Duarte Gondim; Claudio Gabriel Lima Junior (The Journal of Engineering and Exact Sciences)
The global chemical industry is under increasing pressure to adopt more sustainable practices, as most chemical products exceed environmental safety limits. Given that chemical production largely relies on catalytic processes, the development of solid acid catalysts has become crucial for more sustainable production. Among these catalysts, niobium pentoxide stands out due to its strong acid sites, which remain active in the presence of water, and its stability under hydrothermal conditions. Recent studies have demonstrated that these solids maintain their catalytic activity even in the presence of strong bases, making them unique catalysts. This review explores the potential of niobium pentoxide as an acid catalyst, addressing advances in synthesis techniques, surface modifications, and combinations with other materials to enhance its catalytic performance in sustainable applications, such as biomass conversion and biofuel production, opening new pathways for the production of greener chemicals. Finally, the future perspectives of niobium pentoxide - based catalysts in green chemistry are discussed.